Factors Related to Maternal Mortality in Yogyakarta City: Descriptive Analysis from 2015 to 2021 - Nisya Zahra Safitri; Nur Syakilah; Nur Tri Septianingsih; Nuramalia Khumaira A; Regita Alifia Maharani A; Rezki Amalia Maharani (Journal of Health Science and Pharmacy, 2026)
Background: The Maternal Mortality Rate (MMR) in Indonesia remains alarmingly high. MMR is a critical indicator of public health, reflecting the number of women who die due to pregnancy-related complications, including childbirth and treatment-related issues, within 42 days postpartum, excluding accidents or incidental causes. This rate is measured per 100.000 live births (Ministry of Health of the Republic of Indonesia & Measure DHS ICF International, 2012). MMR serves as a measure of the effectiveness of maternal health programs, and its reduction is a key objective of public health strategies. Objective: This study aims to examine the distribution of maternal deaths in Yogyakarta City from 2015 to 2021, using secondary data sourced from the Yogyakarta City Health Profile. Method: The study employs a quantitative descriptive approach, analyzing secondary data obtained from the Yogyakarta City Health Profile. The data include the number of maternal deaths recorded annually. The analysis was conducted by organizing the data into tables and graphs, followed by a narrative interpretation to identify trends and patterns in maternal mortality rates. Results: The study found fluctuations in the maternal mortality rate from 2015 to 2021. While the MMR showed some stability, it remained high, indicating ongoing challenges in maternal health. The rate is influenced by various factors, including nutritional status, socio-economic conditions, pre-existing health conditions, pregnancy complications, and access to healthcare. Conclusion: The fluctuations in maternal mortality rates in Yogyakarta City highlight persistent challenges in improving maternal health despite relatively adequate healthcare infrastructure. These findings underscore the need to strengthen maternal and neonatal health services, enhance referral systems, and improve access to healthcare, particularly in remote areas. Community-based interventions and data-driven policies are crucial to achieving sustainable health development goals. Keywords: Maternal Mortality Rate, Challenges of MMR Control, Responses and Efforts to Reduce, Yogyakarta City